Translators through History - Pulido Correa, Martha Lucía; García Barrera, Sebastián (Íkala, Revista de Lenguaje y Cultura, 2004)
The aim of this article is to describe the various steps involved in our work of translation on the History of Translation. It also intends to bring to the fore the distinctive characteristics of this particular book, whose source writing has been marked by discoursive multiplicity. Received: 17-02-04 / Accepted: 29-04-04 How to reference this article: Pulido Correa, M. L. & García Barrera, S. (2004). À propos de la traduction des Traducteurs dans l’histoire / Translators through History. Íkala. 9(1), pp. 271 – 285